Efficacy of Topical Antifungal Nail Solution Versus Topical Placebo Solution for the Treatment of Pedal Onychomycosis: A Randomized Controlled Trial - Donald Scot Malay; Hye Rin Kim; Nicholas John Perfetti; Yolanda R. Marshall; Peter J. Bregman; Allysa M. Vavra (Infectious Diseases and Therapy)
Abstract Introduction Pedal onychomycosis is common, and its treatment entails debridement combined with topical and/or oral antifungal medication. Methods In this study, 69 participants were randomly allocated to either active (31 [44.93%]) or placebo (38 [55.07%]) topical solution. The primary outcome was mycological cure, and secondary outcomes included visible nail plate involvement and toenail-related quality of life. Results After a minimum duration of follow-up of 7 months and a maximum of 9 months, participants in the active solution group experienced statistically significantly greater mycological cure (1 [2.63%] placebo versus 17 [54.84%] active, p < 0.0001) and clinical cure (2 [5.56%] placebo versus 21 [70%] active, p < 0.0001), including 47.62% of which showed complete clearance of visible nail plate involvement with no residual gross nail plate dystrophy and improved toenail-related quality of life, including less symptom bothersomeness (p < 0.0344), less overall toenail problems (p < 0.0315), and greater satisfaction with treatment (p < 0.0195) as early as the 3-month follow-up visit. In addition, the active solution group experienced less frequent symptoms (p = 0.0046 at 9 months) and symptom bothersomeness (p = 0.0002 at 7 months, < 0.0001 at 9 months), less difficulty caring for toenails and better toenail appearance (p = 0.0250 at 7 months, p= 0.007 at 9 months), improved physical activity and less toenail pain (p = 0.0208 at 7 months, p = 0.003 at 9 months), less overall toenail problems (p = 0.0002 at 7 months, p = 0.0006 at 9 months), and greater treatment satisfaction (p = 0.0003 at 7 months, p = 0.0015 at 9 months). Conclusions Participants with pedal onychomycosis that were randomized to the active topical solution showed statistically significantly greater mycological and clinical cures, as well as improved quality of life, in comparison with those allocated to the placebo topical solution. Trial Registration ISRCTN Protocol no. 77852934.